Combine holts winter and support vector machines in forecasting time serie [electronic resource] - Alfa Mohammed Salisu, 1963-; Ani Shabri (2013)
Thesis (Sarjana Sains (Matematik)) - Universiti Teknologi Malaysia, 2013